Analisis Penerapan Perencanaan Pajak Atas Biaya Kesejahteraan Karyawan - Hafsah Hafsah; Febri Ramadhani (-)
This  research is  the implementation of tax planning for the costs of the welfare of employees to minimize the burden of taxes owed to the tax at PT. Pertani (persero) Medan.  The analysis of this research used descriptive technique analysis data. The  data were collected and arranged, then conducted an analysis of the data.  Descriptive analysis  of data collected in the form of numbers. This is due to the quantitative method.  PT. Pertani has done the implementation of tax planning  on  employees  welfare costs but the effort is not maximized because there are still policies related to the costs of employees welfare which is a costs that can not be charged as a deduction of company's gross income (non deductible) . The company policy regarding of employees welfare costs, among others are :  PT. Pertani doesnt bear outcome added tax according to section 21 pph about employees.The company establishes its own clinic where the costs incurred by the company for the provision of doctors and the provision of medicines to employees can not  be  deducted from gross income.